2019
DOI: 10.13005/bpj/1761
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Syzygium Cumini Seed Extracts in Alleviating Arsenic-Induced Hepatotoxicity and Blood Cell Genotoxicity in Wistar Albino Rats

Abstract: Syzygium cumini is well known for its medicinal values in the indigenous Indian system of medicine. This study was designed to evaluate the protective effect of methanolic (SCM), ethanolic (SCE) and aqueous (SCA) extracts of Syzygium cumini seeds on arsenic-induced blood cell genotoxicity and hepatotoxicity in Wistar albino rats. Rats were divided into five groups: (1) control, (2) arsenic, (3) SCM, (4) SCE and (5) SCA. After completion of 60 days treatment period, comet assays were performed on isolated blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Our findings revealed that SA increased ALT and ALP activities in rats. This finding corroborates previous reports in which SA increased the activities of these enzymes in the blood of animals [ 32 , [46] , [47] , [48] , [49] ]. However, co-administration of SA with ELVp restored AST, ALT and ALP activities comparable with control.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings revealed that SA increased ALT and ALP activities in rats. This finding corroborates previous reports in which SA increased the activities of these enzymes in the blood of animals [ 32 , [46] , [47] , [48] , [49] ]. However, co-administration of SA with ELVp restored AST, ALT and ALP activities comparable with control.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the protective effect of the methanolic extract of S. cumini seeds on the arsenic-induced genotoxicity and hepatotoxicity was also evaluated in albino Wistar rats (Kumar and Thakur, 2018). The oral administration of this extract led to normalization of biochemical variables altered by the action of arsenic [e.g., serum aspartate aminotransferase (AST), alkaline phosphatase (ALP), alanine aminotransferase (ALT) and total concentrations of protein and bilirubin], and significantly restored the activity of enzymatic and non-enzymatic antioxidants of cells [e.g., lipid peroxidation (LPO), superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH)].…”
Section: Discussionmentioning
confidence: 99%
“…), reduces the production of reactive oxygen and peroxide end products MDA, and counteracts oxidative stress (21)(22). Finding natural compounds that have anti-oxidative effects to neutralized oxidative stress is on demand (23). As oxidative stress plays an important contribution in variety diseases such as heart diseases (24).…”
Section: Discussionmentioning
confidence: 99%